Phylogenetic appraisal of antagonistic, slow growing actinomycetes isolated from hypersaline inland solar salterns at Sambhar salt Lake, India - Arul Jose, Polpass; Jebakumar, Solomon R. (Frontiers in Microbiology, 2013)
Inland solar salterns established in the vicinity of Sambhar Lake are extreme saline environments with high salinity and alkalinity. In view of the fact that microbes inhabiting such extreme saline environments flourish the contemporary bioprospecting, it was aimed to selectively isolate slow growing and rare actinomycetes from the unexplored solar salterns. A total of 14 slow growing actinomycetes were selectively isolated from three composite soil samples of inland solar salterns. Among the isolates, four groups were formed according to similarity of the banding patterns obtained by amplified ribosomal DNA restriction analysis (ARDRA). A subset of representative isolates for each ARDRA group was identified using 16S rDNA sequence based phylogenetic analysis and subsequently the entire isolates were assigned under three different genera; Streptomyces, Pseudonocardia and Actinoalloteichus. The genus Streptomyces was found to be the dominant among the isolates. Furthermore, rare actinomycete genus Actinoalloteichus was isolated for the first time from solar saltern. Determination of salt-tolerance revealed that certain level of salt-tolerance and moderate halophilism occurs among the actinomycetes isolated from the inland salterns. In addition, all the acinomycetes were screened in two levels to unravel their ability to produce antimicrobial compounds. Significant antimicrobial activity was found among the actinomycetes against a range of bacteria and fungi to worth further characterization of these persuasive actinomycetes and their antimicrobial secondary metabolites. In a nutshell, this study offered a first interesting insight on occurrence of antagonistic rare actinomycetes and streptomycetes in inland solar salterns associated with Sambhar salt Lake.